2019
DOI: 10.1073/pnas.1906999116
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of IRE1α through its kinase domain attenuates multiple myeloma

Abstract: Multiple myeloma (MM) arises from malignant immunoglobulin (Ig)-secreting plasma cells and remains an incurable, often lethal disease despite therapeutic advances. The unfolded-protein response sensor IRE1α supports protein secretion by deploying a kinase–endoribonuclease module to activate the transcription factor XBP1s. MM cells may co-opt the IRE1α–XBP1s pathway; however, the validity of IRE1α as a potential MM therapeutic target is controversial. Genetic disruption of IRE1α or XBP1s, or pharmacologic IRE1α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 52 publications
3
81
0
Order By: Relevance
“…Importantly, ectopic LDTM expression significantly enhanced the growth of KMS11 tumor xenografts in vivo (Figure 5B). Furthermore, while IRE1 depletion by shRNA inhibited KMS11 cell growth both in vitro and in vivo, in keeping with the cytoprotective role of this UPR sensor (Harnoss et al, 2019), expression of LDTM nevertheless accelerated growth even in the context of IRE1 knockdown (Figure 5A and B), consistent with LDTM’s ability to improve cell viability independent of full-length IRE1. A single-cell-derived KMS11 clone expressing the same LDTM construct exhibited a similar enhancement in tumor growth (Figure 5—figure supplement 1A), as did a clone expressing the more precise 1–507 cleavage product (Figure 5—figure supplement 1B).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Importantly, ectopic LDTM expression significantly enhanced the growth of KMS11 tumor xenografts in vivo (Figure 5B). Furthermore, while IRE1 depletion by shRNA inhibited KMS11 cell growth both in vitro and in vivo, in keeping with the cytoprotective role of this UPR sensor (Harnoss et al, 2019), expression of LDTM nevertheless accelerated growth even in the context of IRE1 knockdown (Figure 5A and B), consistent with LDTM’s ability to improve cell viability independent of full-length IRE1. A single-cell-derived KMS11 clone expressing the same LDTM construct exhibited a similar enhancement in tumor growth (Figure 5—figure supplement 1A), as did a clone expressing the more precise 1–507 cleavage product (Figure 5—figure supplement 1B).…”
Section: Resultssupporting
confidence: 63%
“…Thus, the production of LDTM upon caspase-mediated cleavage of IRE1 can significantly improve the fitness of cancer cells to survive and grow in stressful microenvironments. This conclusion has important potential implications for the role of IRE1 in hematopoietic malignancies such as MM, because it suggests that IRE1 promotes tumor growth not only in its general role as a cytoprotective UPR mediator (Harnoss et al, 2019) but also in particular through its caspase-driven antiapoptotic LDTM product. Our studies open the door to further investigating caspase-mediated processing of IRE1 and other UPR sensors in response to proteotoxic as well as other types of cell stress in settings of health and disease.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, our results showed that PERK inhibition also slightly affected the pro-survival molecules of the two other branches of the UPR, namely XBP1s and ATF6, suggesting that it might also exert an overall anti-UPR inhibitory effect. This was also shown by the total UPR expression profile and post cell-treatment with GSK2606414, which revealed the suppression of major UPR driver genes, including IRE1 ( ERN1 ) and XBP1 , which are key players in MM tumor growth [ 38 , 39 ]. In addition, treatment of MM cells with GSK2606414 downregulated the CEBPB gene, which regulates transcription factors critical for the proliferation and survival of MM cells [ 40 ], and the PPP1R1A gene, which is upregulated by ATF4 and provides a negative feedback loop by dephosphorylating eIF2A [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SYVN1 has been implicated in the oncogenesis of activated B cell-like DLBCL (ABC-DLBCL) [237], and has been considered a potential therapeutic target for restoring the tumor suppressor activity of unstable lymphoma-associated Blimp-1 mutants [237]. In addition, MM cells express high levels of SYVN1 to cope with ER stress resulting from immunoglobulin hyperproduction [238]. Therefore, it would be of great interest to determine whether SYVN1 can be used to design cell type-specific PROTACs to target hematologic malignancies associated with B cells, particularly MM.…”
Section: Identification Of Cell Type-specific/selective E3 Ligasesmentioning
confidence: 99%